STEREOLOGY AND 3D MICROSCOPY: USEFUL ALTERNATIVES OR COMPETITORS IN THE QUANTITATIVE ANALYSIS OF MICROSTRUCTURES? - Exner, Hans Eckart (Image Analysis and Stereology, 2011)
With the rapid development of modern techniques for producing 3D images, the assessment of 3D geometry from 2D sections of projections by stereological methods seems to become more and more redundant. The paper aims to show the limits of the two approaches and to outline their relative advantages in practical applications. It is concluded that, for a large variety of applications, classical stereological methods are the most effective way to characterize 3D geometry of irregular microstructures. The basic equations for useful global (field) parameters are summarized and their assessment by manual techniques is indicated. For other types of applications asking for complex parameters like shape, arrangement or size distribution, preference should be given to direct 3D measurements. Parameters obtained by 2D analysis of sections or projections are useful for comparison purposes, for empirical correlation analysis or for fingerprinting-type description. Field and feature parameters and the problems of data reductions are discussed.